Early Response to COVID-19 in the Philippines - Amit, Arianna Maever L (Archīum Ateneo, 2021)
Low- and middle-income countries (LMICs) with weak health systems are especially vulnerable during the COVID-19 pandemic. In this paper, we describe the challenges and early response of the Philippine Government, focusing on travel restrictions, community interventions, risk communication and testing, from 30 January 2020 when the first case was reported, to 21 March 2020. Our narrative provides a better understanding of the specific limitations of the Philippines and other LMICs, which could serve as basis for future action to improve national strategies for current and future public health outbreaks and emergencies.